A Parental Empathy Communication in Children’s Education Patterns - Zubaili, Zubaili (Jurnal Al-Fikrah, 2023)
A child is born helpless, in a state of complete dependence on other people, unable to do anything and even unable to help himself. He was born in a state of purity and fitrah, but it is the parents who give the color of life to their children. The family is the first and foremost environment for children, which contributes to the mental and physical development and growth in their lives. Through interactions within the family, children not only identify (integrate) themselves with the life of society and the natural surroundings. The ability to recognize other people’s emotions (empathy) is the ability to understand the feelings and needs of others, so that other people will feel happy and understand their feelings. This research includes library research. The results of the study found that parents are responsible for meeting children’s biological and psychological needs, including a sense of security, affection, and understanding as children. However, often the lack of communication between parents and children can lead to a lack of confidence and empathy in children. To anticipate this, parents need to improve empathetic communication with their children and create an interesting atmosphere in communicating, both at home and outside the home, such as involving children in fun activities such as hanging out and going for walks. If parents are unable to create an interesting atmosphere for children, it will be difficult to implement empathetic communication.